(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The utilization of recycled aggregate in concrete production has gained significant attention due to its potential environmental and economic benefits. However, one of the major challenges associated with recycled aggregate concrete (RAC) is its susceptibility to moisture absorption, which can negatively affect its durability and mechanical properties. To address this issue, various hydrophobic treatments have been investigated to enhance the performance of RAC. This literature survey aims to provide an overview of the research conducted on the impact of different hydrophobic treatments on the properties of RAC. The survey begins by discussing the importance of hydrophobic treatments in improving the resistance of RAC to moisture ingress and the subsequent effects on its mechanical strength, durability, and dimensional stability. The survey further explores the different types of hydrophobic treatments employed, including surface coatings, impregnation with hydrophobic agents, and incorporation of hydrophobic admixtures in the concrete mix. The effectiveness of these treatments in reducing water absorption, improving compressive strength, enhancing freeze-thaw resistance, and minimizing drying shrinkage is analyzed based on the findings of various experimental studies and case studies. Additionally, the survey highlights the influence of key factors such as treatment methods, dosages, curing conditions, and aggregate characteristics on the performance of hydrophobically treated RAC. Furthermore, the limitations and challenges associated with hydrophobic treatments in RAC are discussed, along with potential avenues for future research. Overall, this literature survey provides valuable insights into the impact of different hydrophobic treatments on the properties of RAC, offering a comprehensive understanding of the current state of research in this field and paving the way for the development of more durable and sustainable concrete structures incorporating recycled aggregates.